I Wouldn't Let it Get to Me: Pregnant Black Women's Experiences of Discrimination. Issue 3 (May 2021) - Dove-Medows, Emily; Thompson, Lucy; McCracken, Lindsey; Kavanaugh, Karen; Misra, Dawn P.; Giurgescu, Carmen
Abstract: Purpose: Non-Hispanic Black women in the United States experience disproportionately higher rates of adverse birth outcomes including preterm birth and low birth weight infants compared with White women. Racial discrimination has been associated with these adverse outcomes. However, not all Black women experience discrimination in the same way. The majority of studies that report on the relationship between racial discrimination and maternal health have used quantitative methods that may present a monolithic understanding of this relationship. Qualitative methods, specifically those that incorporate intersectionality, may illuminate the nuances in pregnant Black women's experiences of discrimination. We present a qualitative analysis of Black women's experiences of racial discrimination and pregnancy to shed light on some of these complexities. Study Design and Methods: Qualitative interviews that addressed racial discrimination and pregnancy were conducted as part of a larger study of pregnant Black women that examined social support, neighborhood disorder, and racial discrimination. Interviews were coded for descriptions of racial discrimination and within and across case analysis was conducted. Results: Women described varying experiences of racial discrimination in different contexts. Shielding emerged as a recurring theme in women's accounts of dealing with racial discrimination during pregnancy. Clinical Implications: Nurses engaged in maternity care need an understanding of how pregnant Black women experience racial discrimination in different ways. Black women may be likely to take personal responsibility for managing discrimination-related stress in pregnancy as a consequence of direct experiences of discrimination. Nurses can support pregnant Black women by recognizing varied experiences of racial discrimination, and by not blaming them for experiences or potential resultant outcomes. Abstract : Black women in the United States experience disproportionately higher rates of adverse birth outcomes including preterm birth and low birth weight infants compared with White women. Racial discrimination has been associated with adverse birth outcomes. In this qualitative study, new insight into the nuanced ways in which Black pregnant women experience racial discrimination are presented.